Mengembalikan Tanggung Jawab Negara dalam Pendidikan: Kritik Terhadap Liberalisasi Pendidikan dalam Uu Sisdiknas dan Uu Bhp - Victor Nalle Williamson Nalle (The Constitutional Court of the Republic of Indonesia, 2011)
Indonesia’s Constitution has mandated that the state has a goal to develop nation’s intellectual. In that framework, the state should have responsibility for the education of the whole people of Indonesia. But by globalization, through the WTO and GATS, Indonesia has been directed toward the liberalization of education. Liberalization is done through legislation that directs the autonomy of state-owned educational institutions, maximizing the role of communities in the state and minimize the role of the state, the format of “Badan Hukum Pendidikan” for all educational institutions, and opening the world of education for foreign educational institutions.